Contested Colonial Metrological Sovereignty: The Daching Riot And The Regulation Of Weights And Measures In British Malaya - Por, Heong Hong (Cambridge University Press, 2021)
Drawing on materials from the National Archives of Malaysia, newspapers, literature on historical metrology, and the colonial history of Malaya, this article weaves a social history of Malaya’s colonial metrological reform by taking into account the roles of both European and Asian historical actors. Prior to the 1894 reform, people in Malaya used customary scales and weight units, which varied across districts, for commercial transactions. Initiated by colonial administrators, the reform was both welcomed and resisted. In 1897, a riot against the Sanitary Board broke out in Kuala Lumpur for its attempt to mandate that previously exempted traders use only government-verified and -stamped scales. The colonial government managed to maintain order and restore its authority at the end of the riot, but four types of merchants goldsmiths, silversmiths, opium dealers, and drug sellers managed to remain exempted. Metrological reform continued to be contested in the following century, but the central concerns of the regulation moved from easing taxation, facilitating cross-district trade, and taming Chinese traders to protecting consumers.